“I ONLY READ A PAGE OR TWO”: NARRATIVE FROM TWO DIFFERENT LANGUAGE LEARNERS - Valisneria Utami (E-LINK JOURNAL, 2022)
Literacy is not only defines as the ability of reading and write but also it is the ability to think critically and cultivate information. This study aims to analyze the literacy experiences of L1 and L2 English speakers. This study interviewed two language speakers, J a native English speaker, and K a non-native English speaker. The result showed that despite the differences in learning English as L1 and L2, some similarities are discovered. The interview, showed that learning English as L1 and L2, both are required cognitive skills and learning strategies. However, for L2 learners, it demands more than just studying the language. To get maximum results, the language should be practiced outside of the classroom. One of the techniques is by practicing extensive reading has been shown to expand vocabulary knowledge and grow motivation in second language learning. Thus, some implications for English teachers in EFL contexts are carried out. Keywords: second language literacy; second language learner